2019
DOI: 10.3390/antibiotics9010013
|View full text |Cite
|
Sign up to set email alerts
|

In the Right Light: Photodynamic Inactivation of Microorganisms Using a LED-Based Illumination Device Tailored for the Antimicrobial Application

Abstract: Drug-resistant bacteria threaten the health of people world-wide and cause high costs to their health systems. According to Scientific American, the number of regrettable fatalities due to the bacteria that are resistant to conventional antibiotics will sum up to 300 million until 2050 if the problem is not tackled immediately. Photodynamic Inactivation (PDI) has proven effective against microorganisms irrespective of their resistance to conventional treatment, but for the translation into clinical practice, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Light emitting diodes (LEDs) technologies have become increasingly feasible and advantageous in potential applications of the food industry due to its low radiant heat emissions, long life expectancy, flexibility and mechanical robustness (D'Souza et al, 2015). Photodynamic inactivation (PDI), based on the use of photosensitizers activated by an appropriate wavelength light, utilizes the photosensitizermediated and light-induced overproduction of reactive oxygen species (ROS) to inactivate the foodborne and food spoilage bacteria (Penha et al, 2017;Hasenleitner & Plaetzer, 2019). A light source of suitable wavelength, photosensitizer and oxygen are the essential components for the PDI .…”
Section: Introductionmentioning
confidence: 99%
“…Light emitting diodes (LEDs) technologies have become increasingly feasible and advantageous in potential applications of the food industry due to its low radiant heat emissions, long life expectancy, flexibility and mechanical robustness (D'Souza et al, 2015). Photodynamic inactivation (PDI), based on the use of photosensitizers activated by an appropriate wavelength light, utilizes the photosensitizermediated and light-induced overproduction of reactive oxygen species (ROS) to inactivate the foodborne and food spoilage bacteria (Penha et al, 2017;Hasenleitner & Plaetzer, 2019). A light source of suitable wavelength, photosensitizer and oxygen are the essential components for the PDI .…”
Section: Introductionmentioning
confidence: 99%
“…The interest in relatively large field illuminations for PDDI of skin infections motivated the development of LED devices tailored for methylene blue (635 ± 11.5 nm) and for sodium magnesium chlorophylin (433 ± 10.5 nm) [ 302 ]. This later dye is a food additive and is of interest for the photodisinfection of food.…”
Section: Light Sources For Pddimentioning
confidence: 99%
“…Sodium magnesium chlorophyllin (SMC), a derivative of chlorophyll, has many advantages, such as good water solubility, high affinity to biomolecules, excellent photosensitivity and rapid elimination from the body with no adverse reactions. In addition, it is reported that PDI based on SMC (10 µmol/L) reduced the number of viable S. aureus by more than 6 log CFU/ mL [20]. Therefore, SMC has potential application as a photosensitizer used in PDI to eradicate pathogens on food products.…”
Section: Introductionmentioning
confidence: 99%